2018
DOI: 10.6007/ijarafms/v8-i3/5010
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Entrepreneurial Leadership and School Effectiveness among Secondary Schools

Abstract: There is a general consensus among stakeholders in education that a strong positive educational leadership is a determining factor of school effectiveness. However, many questions were raised as regards to the applicability of entrepreneurial leadership in the context of education. The main purpose of this study is to determine the relationship between entrepreneurial leadership and school effectiveness, and also to identify the dimension of entrepreneurial leadership that contributes more to school effectiven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 20 publications
(29 reference statements)
1
4
0
Order By: Relevance
“…Principals full play to the explore ability, miner ability, integrator ability, and accelerator ability to enhance organizational effectiveness from a student development perspective, teachers' satisfaction perspective, and organization management perspective. This result also resonates with the previous argument, which confirmed entrepreneurial leadership impacts on school performance and school effectiveness (Dahiru et al, 2017;Lope Pihie et al, 2018;Kasim and Zakaria, 2019;Ghazali et al, 2020), as well as organizational performance and effectiveness (Ruvio et al, 2010;Fontana and Musa, 2017;Sari and Ahmad, 2022). Other than that principals in organizations with a high level of entrepreneurial leadership behavior are more willing to enhance the organizational adaptability of the uncertain environment, discover and explore strategic value creation, and create new operating models to lead to an increase in the level of organizational effectiveness.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Principals full play to the explore ability, miner ability, integrator ability, and accelerator ability to enhance organizational effectiveness from a student development perspective, teachers' satisfaction perspective, and organization management perspective. This result also resonates with the previous argument, which confirmed entrepreneurial leadership impacts on school performance and school effectiveness (Dahiru et al, 2017;Lope Pihie et al, 2018;Kasim and Zakaria, 2019;Ghazali et al, 2020), as well as organizational performance and effectiveness (Ruvio et al, 2010;Fontana and Musa, 2017;Sari and Ahmad, 2022). Other than that principals in organizations with a high level of entrepreneurial leadership behavior are more willing to enhance the organizational adaptability of the uncertain environment, discover and explore strategic value creation, and create new operating models to lead to an increase in the level of organizational effectiveness.…”
Section: Discussionsupporting
confidence: 87%
“…Entrepreneurial leadership attributes enhance organizational performance, achievement and effectiveness for future development (Fontana and Musa, 2017;Liu and Xi, 2021). According to the literature findings, principal entrepreneurial leadership has a significant relationship with school effectiveness (Dahiru et al, 2017;Lope Pihie et al, 2018), performance, and quality (Ruvio et al, 2010;Kasim and Zakaria, 2019;Ghazali et al, 2020). Nonetheless, the relationship between principal entrepreneurial leadership and organizational effectiveness in the education field has not received enough attention from scholars.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Thornberry (2006), Gupta et al (2004), Kuratko (2007), and Schein (2010) posited a variety of different perceptions and dimensions in their theories while discussing entrepreneurial leadership in an organization. Whatever the definition may be, it is clear that entrepreneurial leadership is one of the most desirable and effective forms of leadership to be implemented in the modern educational environment (Abbas and Zaidatol Akmaliah, 2016; Kavitha and Zaidatol Akmaliah, 2017; Pihie et al, 2018). However, the implementation of entrepreneurial leadership practices needs to be further explored by educational administrators, especially for schools operating under the purview of highly centralized policies.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, school principals must consider and plan time for the extra work necessary for instilling entrepreneurial leadership among school administrators (Leonard, 2013; Reeves, 2007). Although the previous literature has highlighted the positive impact of entrepreneurial leadership in schools holistically (Pihie et al, 2018; Xaba and Malindi, 2010; Yemini and Sagie, 2015), the actual practices of this leadership in helping centralized schools to raise funds for school purposes are scarcely discussed.…”
Section: Introductionmentioning
confidence: 99%
“…According to a study of secondary school students, students with high GPAs have more positive attitudes toward entrepreneurship. This is because the students are motivated and eager to learn new subjects (Pihie et al, 2018). However, another study has shown a negative relationship between a higher GPA and an intention to entrepreneurship (Sun et al, 2020).…”
Section: Discussionmentioning
confidence: 99%